IN VITRO ANTICANDIDAL ACTIVITY OF PIMENTA DIOICA (ALLSPICE) ESSENTIAL OIL AGAINST CLINICAL ISOLATES OF CANDIDA ALBICANS AND NON-ALBICANS CANDIDA: Life Science-Microbiology - KAMBLE, VILAS A. (International Journal of Life Science and Pharma Research, 2012)
The antimicrobial property of volatile aromatic oils from medicinal as well as other edible plants has been recognized since antiquity. Candida species are an important cause of opportunistic infections in the oral cavity of immunocompromised patients and vaginal candidiasis. The antifungal activity of the essential oil of Pimento dioica (allspice oil) was investigated against 75 clinical isolates of Candida albicans and non-albicans Candida. Sensitivity profile of clinical isolates to undiluted and diluted (3:1, 2:2 and 1:3) allspice oil was evaluated by disc diffusion method. Minimum inhibitory concentrations (MIC) and minimum fungicidal concentrations (MFC) were evaluated by broth microdilution and broth macrodilution method. Allspice oil effectively inhibited all clinical isolates of C. albicans and non-albicans Candida with growth inhibition zones ranging from 24 to 44 mm. Allspice oil inhibited C. albicans growth with mean minimum inhibitory concentration (MIC) of 0.98 µl/ml (v/v) and 1.14 µl/ml (v/v) by broth micro dilution and broth macrodilution method, respectively. The clinical isolates of C. albicans required as high as 1.25 µl/ml (v/v) concentration of allspice oil for its inhibition by both methods. The isolates of non-albicans Candida showed MIC range of 0.15 – 2.50 µl/ml (v/v) by broth microdilution and 0.31 – 2.50 µl/ml (v/v) broth macrodilution. The isolates of C. krusei exhibited higher sensitivity to allspice oil than other isolates with lowest MIC of 0.15 µl/ml (v/v).